2011
DOI: 10.1016/j.jconrel.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Oral TNF-α gene silencing using a polymeric microsphere-based delivery system for the treatment of inflammatory bowel disease

Abstract: The purpose of this study was to evaluate down-regulation of tumor necrosis factor (TNF)-α by oral RNA interference therapy. Control (scrambled sequence) or TNF-α specific small interfering RNA (siRNA) was encapsulated in type B gelatin nanoparticles and further entrapped in poly(epsilon-caprolactone) (PCL) microspheres to form a nanoparticles-in-microsphere oral system (NiMOS). Upon confirmation of the dextran sulfate sodium (DSS)-induced acute colitis model, mice were divided into several treatment groups re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 39 publications
4
113
0
Order By: Relevance
“…The therapeutic effects of TNF-α NiMOS were reflected in increased body weight and reduced levels of MPO in colitis-induced mice. 81 These results demonstrated that NiMOS is a promising formulation for oral siRNA delivery in IBD treatment. NiMOS increased the loading capacity of siRNA due to the structural design of the delivery system.…”
mentioning
confidence: 75%
“…The therapeutic effects of TNF-α NiMOS were reflected in increased body weight and reduced levels of MPO in colitis-induced mice. 81 These results demonstrated that NiMOS is a promising formulation for oral siRNA delivery in IBD treatment. NiMOS increased the loading capacity of siRNA due to the structural design of the delivery system.…”
mentioning
confidence: 75%
“…Successful intracellular and intranuclear delivery of the stable NF-κB decoy to the site of inflammation and action in GI tract is a field yet to be explored (Tahara et al, 2011). Finaly, RNA interference therapy utilizing short interfering (siRNA), usually composed of 20-25 nucleotides targeted to cytosol will trigger gene silencing mechanism through RNA interference where siRNA can block the expression of a specific gene (TNF-or different proinflammatory gene expression in IBD) and proinflammatory protein synthesis, thus providing for successful therapeutic approach in IBD (Kriegel & Amiji, 2011). Gene therapy can be delivered to local sites in GI tract, produce and concentrate a therapeutic protein in intestinal tissue, and release negligible amounts into the circulation (Kriegel & Amiji, 2011).…”
Section: Biological and Gene Therapies For Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Finaly, RNA interference therapy utilizing short interfering (siRNA), usually composed of 20-25 nucleotides targeted to cytosol will trigger gene silencing mechanism through RNA interference where siRNA can block the expression of a specific gene (TNF-or different proinflammatory gene expression in IBD) and proinflammatory protein synthesis, thus providing for successful therapeutic approach in IBD (Kriegel & Amiji, 2011). Gene therapy can be delivered to local sites in GI tract, produce and concentrate a therapeutic protein in intestinal tissue, and release negligible amounts into the circulation (Kriegel & Amiji, 2011). Examples presented through literature for design approaches for gene, peptide and protein targeting in IBD relay on the previous experience with nano-and micro-carriers for inflammation and vaccine non specific or specific targeting.…”
Section: Biological and Gene Therapies For Inflammatory Bowel Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical goals of IBD treatment are to control inflammation, achieve mucosal healing, and reduce surgeries and hospitalizations [2,3]. Traditional treatment strategies have been limited to the daily administration of high doses of medications, including biologic therapies, corticosteroids, immunomodulators, aminosalicylates, and antibiotics [4,5]. Although some of these medications have proven effective in initially alleviating IBD, their long-term application had been largely restricted by poor efficacy and serious side effects [6].…”
Section: Introductionmentioning
confidence: 99%